Factors Associated with Gestational Diabetes Mellitus: A Meta-Analysis - Yu Zhang; Cheng-Ming Xiao; Yan Zhang; Qiong Chen; Xiao-Qin Zhang; Xue-Feng Li; Ru-Yue Shao; Yi-Meng Gao (Journal of Diabetes Research)
Gestational diabetes mellitus (GDM) is a major public health issue, and the aim of the present study was to identify the factors associated with GDM. Databases were searched for observational studies until August 20, 2020. Pooled odds ratios (ORs) were calculated using fixed- or random-effects models. 103 studies involving 1,826,454 pregnant women were identified. Results indicated that maternal age≥25 years (OR: 2.466, 95% CI: (2.121, 2.866)), prepregnancy overweight or obese (OR: 2.637, 95% CI: (1.561, 4.453)), family history of diabetes (FHD) (OR: 2.326, 95% CI: (1.904, 2.843)), history of GDM (OR: 21.137, 95% CI: (8.785, 50.858)), macrosomia (OR: 2.539, 95% CI: (1.612, 4.000)), stillbirth (OR: 2.341, 95% CI: (1.435, 3.819)), premature delivery (OR: 3.013, 95% CI: (1.569, 5.787)), and pregestational smoking (OR: 2.322, 95% CI: (1.359, 3.967)) increased the risk of GDM with all P<0.05, whereas history of congenital anomaly and abortion, and HIV status showed no correlation with GDM (P>0.05). Being primigravida (OR: 0.752, 95% CI: (0.698, 0.810), P<0.001) reduced the risk of GDM. The factors influencing GDM included maternal age≥25, prepregnancy overweight or obese, FHD, history of GDM, macrosomia, stillbirth, premature delivery, pregestational smoking, and primigravida.